Proposed new interior design scheme of Baba Nyonya Boutique Hotel, at existing 3 storey shophouse Lot 38, 41, & 42 at Lorong Hang Jebat, Bandar Hilir ,Melaka, For Mr.Cheong Chey Yin @ Lauraen / Siti Zulaikha Mohmad Zin - Mohmad Zin, Siti Zulaikha (Faculty of Architecture, Planning and Surveying, 2012)
This project is about proposed new design of Baba Nyonya boutique hotel at existing 3 storey shophouse Lot 38, 41 and 42 at Lorong Hang Jebat, Banda Hilir, Melaka. The total area of this building is around 9352 square feet. It was divided into ground floor, first floor and second floor. The location is strategic because this site was located at the center of Melaka. As we know, Melaka is a small state and it rich with historical buildings. It is located on one of the oldest of Melaka named Heeren Street by the Dutch. Most of the economy sources of Melaka depend on their tourism. Melaka sit upon the southwestern coast of the Malay Peninsula opposite Sumatera, with the state of Negeri Sembilan to the north and the Johor to the east. The focus of this study is to analyze and to understand the interior design element in Baba Nyonya shophouse. Baba Nyonya is one of unique ethnic in Malaysia. Shophouse is one of the heritage building in Malaysia. Government have their own method to keep and to save this asset for the future generation. This study will be carry on one case study to get two types of data involved such as the primary and secondary data. In the primary data, researchers get the data by doing four types of measurement such as on-site observation, on-site measurement, interview with the expert, and questionnaire. In secondary data, researchers get the data from the reading the books, unpublished thesis, articles, magazines, journal, newspaper and research on internet.